2018
DOI: 10.5005/jp-journals-10025-1166
|View full text |Cite
|
Sign up to set email alerts
|

Epithelium-on Corneal Cross-linking for Progressive Keratoconus: Two-year Outcomes

Abstract: Corneal cross-linking (CXL) has been established as a successful treatment tool for the treatment of progressive keratoconus in terms of slowing or halting progressive corneal steepening and thinning and even on some occasions, reversing the steepening. To date the Dresden epithelium-off protocol is regarded as the gold standard and the epithelium-on (epi-on) approaches have met with less success. Both doctors and patients would welcome an epi-on CXL procedure that provided good outcomes as the morbidity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Besides these investigations, other CXL protocols have been evaluated that are based on the epi-on concept, such as the CXLO protocol that uses a new sodium iodide riboflavin formulation that theoretically allows a greater level of penetration [47][48][49][50][51]. ese investigations have shown that the use of the CXLO protocol can halt the progression of ectasia and result in better visual acuity without the risk associated to epi-off CXL [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Besides these investigations, other CXL protocols have been evaluated that are based on the epi-on concept, such as the CXLO protocol that uses a new sodium iodide riboflavin formulation that theoretically allows a greater level of penetration [47][48][49][50][51]. ese investigations have shown that the use of the CXLO protocol can halt the progression of ectasia and result in better visual acuity without the risk associated to epi-off CXL [47][48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%